2021
DOI: 10.1080/22423982.2021.1909333
|View full text |Cite
|
Sign up to set email alerts
|

Neural-level associations of non-verbal pragmatic comprehension in young Finnish autistic adults

Abstract: This video-based study examines the pragmatic non-verbal comprehension skills and corresponding neural-level findings in young Finnish autistic adults, and controls. Items from the Assessment Battery of Communication (ABaCo) were chosen to evaluate the comprehension of non-verbal communication. Inter-subject correlation (ISC) analysis of the functional magnetic resonance imaging data was used to reveal the synchrony of brain activation across participants during the viewing of pragmatically complex scenes of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Research in pragmatics has also been demonstrated to correlate with the clusters identified in our scientometric analysis. Among these studies are those investigating variations in pragmatic language learning in non-English contexts [ 145 ], aspects of politeness [ 146 ], using virtual reality for developing pragmatic language [ 147 ], pragmatics and reasoning [ 148 ], ritual interaction [ 132 ], hearing impairment and pragmatic language skills [ 149 ], autism and neural association of pragmatic language skills [ 150 ], linguistic prediction at the pragmatic language level [ 151 ], mind reading in pragmatics [ 152 , 153 ] and executive functions and pragmatic language skills [ 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in pragmatics has also been demonstrated to correlate with the clusters identified in our scientometric analysis. Among these studies are those investigating variations in pragmatic language learning in non-English contexts [ 145 ], aspects of politeness [ 146 ], using virtual reality for developing pragmatic language [ 147 ], pragmatics and reasoning [ 148 ], ritual interaction [ 132 ], hearing impairment and pragmatic language skills [ 149 ], autism and neural association of pragmatic language skills [ 150 ], linguistic prediction at the pragmatic language level [ 151 ], mind reading in pragmatics [ 152 , 153 ] and executive functions and pragmatic language skills [ 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…ISC analysis is a method of collectively analyzing shared brain activity, which can be used to quantify the degree to which a subject’s brain activity is similar to that of other subjects ( Hasson et al, 2004 ; Simony et al, 2016 ). Previous studies on ISCs to natural stimuli used audiovisual stimuli such as film ( Hasson et al, 2008 ; Kauppi et al, 2010 ; Dmochowski et al, 2012 ; Tu et al, 2019 ; Bolton et al, 2020 ; Gruskin et al, 2020 ; Patel et al, 2021 ; Ou et al, 2022 ), television/video ( Cantlon and Li, 2013 ; Schmälzle et al, 2013 ; Chen and Farivar, 2020 ; Kotila et al, 2021 ), stories ( Wilson et al, 2008 ; Finn et al, 2018 ; Lerner et al, 2018 ; Cohen et al, 2022 ), speech ( Schmälzle et al, 2015 ), and audio ( Kandeepan et al, 2020 ; Thiede et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in statistical methods and meta-analysis have allowed the incorporation of big data into human imaging (Pando-Naude et al, 2021). Using techniques of the activation likelihood estimation (ALE; Laird et al, 2010) methodology, a coordinatebased algorithm for meta-analysis of neuroimaging studies, Pando-Naude et al (2021) conducted a coordinate-based meta-analysis of a wide range of functional magnetic resonance imaging (fMRI) studies. The results revealed that music perception involves the right superior temporal gyrus (STG), left superior frontal gyrus, left medial frontal gyrus, right lentiform nucleus (putamen), left lentiform nucleus (putamen), caudate, left cerebellum, left insula, and right frontal gyrus (Pando-Naude et al, 2021).…”
Section: Introductionmentioning
confidence: 99%